Answer:
[tex]\frac{1}{2}[/tex][tex]t^{2}Sin5t[/tex]
Step-by-step explanation:
using the Convolution theorem to find the inverse of :
[tex]\frac{5}{s^{3}(s^{2}+25 ) }[/tex]
[tex]L^{-1}[/tex] [tex]\frac{5}{s^{3}(s^{2}+25 ) }[/tex] = [tex]\frac{1}{s^{3} }[/tex] × [tex]\frac{5}{s^{2}+25}[/tex]
we know from derivation that
Sin(at) = [tex]\frac{a}{s^{2}+a^{2} }[/tex]
Hence: [tex]\frac{5}{s^{2}+25}[/tex] = Sin5t
Also: [tex]L^{-1}[/tex] [tex]\frac{n!}{s^{n+1} }[/tex] = [tex]t^{n}[/tex]
[tex]L^{-1}[/tex] [tex]\frac{1}{s^{3} }[/tex] = [tex]\frac{1}{2}[/tex] [tex]L^{-1}[/tex] ([tex]\frac{2!}{s^{3} }[/tex])
= [tex]\frac{1}{2}[/tex][tex]t^{2}[/tex]
therefore [tex]L^{-1}[/tex] [tex]\frac{5}{s^{3}(s^{2}+25 ) }[/tex] = [tex]\frac{1}{2}[/tex][tex]t^{2}Sin5t[/tex]